The Influence of Talent Management Practice on Water Resource and Hydropower Company Performance by using the Moderator Effect of Cultural Difference - Visounnarath, Vilaphorn; Hui, Li; Yunlin, Deng; Sarfraz, Muddassar (Chophayom Journal, 2021)
International relations and cooperation between Laos and China have been strengthened under the Belt and Road Initiative, especially the energy sector relevant to the development of water resources and hydropower and the improvement of power system stability. As the development and growth of water resource and hydropower sectors in Laos, these sectors' human resource and HR department have to get ready for coping with changes by improving the HR system and considering the talent management practice (TMP) for increasing energy business performance. The purpose of this study was to determine the TMP influence on water resource and hydropower company performance (WHCP) as well as the cultural difference (CD) that moderated the linkage between TMP and WHCP. A quantitative research method as a questionnaire was developed for data collection at hydropower companies. Investigation of the relationship between TMP independent, CD moderator and WHCP dependent variables were simulated on SPSS software via Correlation and regression analyses (Wording explain: Correlation and Regression are the function in SPSS). The simulation results via Correlation analysis found that three variables were positively interrelated at a significant level (sig.<0.05) which achieved the acceptable hypothesis. The relationship between variables was also found from regression analysis results, which TMP, CD, and the interaction between TMP and CD (TMP.CD) influenced WHCP by 67.4%, 37.7% and 53.7%, respectively. Eventually, the CD moderator variable impacted the relationship between TMP and WHCP as confirmed by TMP.CD that provided its coefficient at Sig. < 0.05 (Sig. = 0.044). Furthermore, it is recommended that the moderation and mediation effects be combined and employed in the research framework of HR/talent management for developing the research in the future. Keyword: Talent Management Practice, Cultural Difference, Moderator Effect, Water Resource and Hydropower Company Performance.